2014
DOI: 10.2217/nnm.13.123
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal Codelivery of A Synergistic Combination of Bioactive Lipids in The Treatment of Acute Myeloid Leukemia

Abstract: Our study provided proof-of-concept evidence to deliver synergistic combination of bioactive lipid to achieve complete remission in AML.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Liposomes evaluated in in vitro or in vivo models Other liposome formulations have been developed for AML treatment, and are designed to avoid adverse effects. For example, a method has been developed for the co-delivery of safingol and C2-ceramide [62]. Safingol is a sphingolipid with antileukemic activity, but is not used in the clinical setting because of its poor water solubility and hemolytic properties [63].…”
Section: Liposomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Liposomes evaluated in in vitro or in vivo models Other liposome formulations have been developed for AML treatment, and are designed to avoid adverse effects. For example, a method has been developed for the co-delivery of safingol and C2-ceramide [62]. Safingol is a sphingolipid with antileukemic activity, but is not used in the clinical setting because of its poor water solubility and hemolytic properties [63].…”
Section: Liposomesmentioning
confidence: 99%
“…were able to reduce significantly the in vitro hemolytic toxicity of safingol and safingol plasma elimination in a mousebased model, and to improve survival in U937-inoculated mice (histiocytic lymphoma cells) [63]. The same authors then developed a co-encapsulation of safingol and C2-ceramide (1:1 molar ratio), another sphingolipid [62]. Given that C2-ceramide and safingol act independently, with different cellular pathways, the authors postulated that coencapsulation of these two sphingolipids would enable them to act in synergistically.…”
Section: Liposomesmentioning
confidence: 99%
“…In a study published in 2014, Tan et al . developed a method to co-encapsulate safingol and C2-ceramide, which are both bioactive sphingolipids that have displayed efficacy against AML but are limited clinically due to hemolytic toxicities (130). The resulting formulation significantly reduced the toxicities presented by the sphingolipids when compared to the free drug and the co-encapsulated formulation extended median survival time from 24 to 37 days compared to the singly encapsulated C2-ceramide (130).…”
Section: Flam – Opening New Doors In Amlmentioning
confidence: 99%
“…developed a method to co-encapsulate safingol and C2-ceramide, which are both bioactive sphingolipids that have displayed efficacy against AML but are limited clinically due to hemolytic toxicities (130). The resulting formulation significantly reduced the toxicities presented by the sphingolipids when compared to the free drug and the co-encapsulated formulation extended median survival time from 24 to 37 days compared to the singly encapsulated C2-ceramide (130). Other liposomal formulations such as liposomal daunorubicin-emetine (a protein synthesis inhibitor) and liposomal GTI-2040 (ribonucleotide reductase-targeting inhibitor) were also developed and examined preclinically against AML cells (131,132).…”
Section: Flam – Opening New Doors In Amlmentioning
confidence: 99%
“…77 Subsequently, a liposomal coencapsulation of safingol/C2-ceramide was developed, which indicated effectivity in vitro and xenograft models, with a dose reduction of 33% compared to liposomal safingol or liposomal C2-ceramide alone. 78 Myhren et al 79 have reported a PEGylated liposome coencapsulating anthracycline daunorubicin (DNR) and emetine with folate modification, which enhanced loading ability than DNR alone. Leukemia stem cell (LSC) with overexpression of miR-126 has been considered as a potential therapeutic target for AML.…”
Section: Approaches Of Nanomedicines For Amlmentioning
confidence: 99%